The Influence of Potential on the Al Microstep Structures and the Fabrication of Combined Structures of ZnO Nanosheets with Al Microsteps and PAAs - Ding, Jian-Ning; Yang, Rong; Liu, Yue-Bin; Yuan, Ning-Yi; Chen, Zhi-Hui; Ding, Gu-Qiao (Nanoscience & Nanotechnology-Asia, 2011)
In this paper, microstep structures fabricated by anode etching on aluminum foil are presented in a mixture electrolyte of 0.05 wt NaCl, 1 wt H3PO4, and 20 ethanol under potentials of 1-40 V at room temperature. The experiment results indicate that the number of microsteps per unit area, the distribution and the ratio of the height to the width of the microsteps are mainly dependent on the potentials. Due to inducement of Al ions, the combined structures of ZnO nanosheets with Al microsteps and porous anodic aluminas (PAAs) are realized by a simple method, which have potential applications in fabrication of nanodevices such as gas sensors and photocatalytic devices.
Keywords: nanosheets